Analisis UUP 1/1974 dan Hukum Islam terhadap Pasal 4 Ayat (2) PERMENDAGRI No. 9 Tahun 2016 tentang Penggunaan SPTJM Nikah Sirri - Nurul Asri Safitri; Titin Suprihatin; Siska Lis Sulistiani (UNISBA Press, 2022)
Abstract. In the legal system in Indonesia, marriage events can be proven through registration carried out at the KUA and the Civil Registration Office. An SPTJM sirri marriage is a statement that serves as a substitute for a marriage certificate/marriage book for those who have not registered their marriage with an authorized institution, indicating the validity of the marriage. The purpose of the study was to determine the analysis of UUP 1/1974 and Islamic law on Article 4 Paragraph (2) PERMENDAGRI No. 9 of 2016 on the use of the SPTJM for unregistered marriages. This study uses a qualitative descriptive method with a normative juridical approach. Primary data sources were obtained from Al-Quran, Hadith, UUP 1/1974, PP 9/1975, KHI, and PERMENDAGRI No. 9 of 2016. Secondary legal sources come from books, journals, and articles related to research. The results of the study suggest The use of the SPTJM for unregistered marriages indicates that it is not in line with UUP 1/1974 and Islamic law because the SPTJM is not authentic evidence and can trigger problems such as not fulfilling the pillars and conditions for a legal marriage, triggering a lot of adultery and same-sex marriages even though the rules are not fulfilled. There are benefits, such as the fulfillment of the rights of a child born from a sirri marriage. Therefore, the harm that arises must be eliminated as per the fiqh rule, which reads